Non-Coding Variants Connect Enhancer Dysregulation with Nuclear Receptor Signaling in Hematopoietic Malignancies - Li, Kailong (Cancer Discov, 2020)
Mutations in protein-coding genes are well established as the basis for human cancer, yet it remains elusive how alterations within non-coding genome, a substantial fraction of which contain cis-regulatory elements (CREs), contribute to cancer pathophysiology. Here, we developed an integrative approach to systematically identify and characterize non-coding regulatory variants with functional consequences in human hematopoietic malignancies. Combining targeted resequencing of hematopoietic lineage-associated CREs and mutation discovery, we uncovered 1,836 recurrently mutated CREs containing leukemia-associated non-coding variants. By enhanced CRISPR/dCas9-based CRE perturbation screening and functional analyses, we identified 218 variant-associated oncogenic or tumor suppressive CREs in human leukemia. Non-coding variants at KRAS and PER2 enhancers reside in proximity to nuclear receptor (NR) binding regions and modulate transcriptional activities in response to NR signaling in leukemia cells. NR binding sites frequently co-localize with non-coding variants across cancer types. Hence, recurrent non-coding variants connect enhancer dysregulation with nuclear receptor signaling in hematopoietic malignancies.